2018
DOI: 10.1111/rda.13194
|View full text |Cite
|
Sign up to set email alerts
|

Subtropical goats ovulate in response to the male effect after a prolonged treatment of artificial long days to stimulate their milk yield

Abstract: The objectives of this study were to determine (i) if in subtropical goats that gave birth during mid-December, the exposition to an artificial long-day photoperiod consisting in only 14 hr of light per day can increase the milk yield and (ii) to test whether these females can respond to the male effect at the end of the prolonged photoperiodic treatment. In experiment 1, 17 lactating goats were maintained under natural short days (control group), while another 22 goats were maintained under artificial long da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…These findings of the current study are consistent with those of others who found milk yield was increased by LDDP in goats [ 3 , 6 , 11 ]. In the present study there was an effect on milk yield over the latter stages of the study whereas there was no effect in the first 6 weeks of exposure to LDPP.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These findings of the current study are consistent with those of others who found milk yield was increased by LDDP in goats [ 3 , 6 , 11 ]. In the present study there was an effect on milk yield over the latter stages of the study whereas there was no effect in the first 6 weeks of exposure to LDPP.…”
Section: Discussionsupporting
confidence: 94%
“…The decline in ovulatory activity during LDPP is supported by Garcia-Hernandez, et al [ 3 ] who looked at reproductive performance at parturition and found that a higher proportion of LDPP goats were pseudo-pregnant compared to goats under natural light conditions which led them to speculate that LDPP was detrimental to reproductive performance. On the other hand, LDPP exposure in goats in the sub-tropics did not decrease ovulation rate in another study [ 11 ]. Rivera et al [ 15 ] found that reproductive activity late in the breeding season had a higher proportion of detached cycles where a silent ovulation occurred, or oestrous behaviour only was observed.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In most areas of the world, goats are mated once yearly in the fall, during their natural mating season, for spring kidding [3][4][5]. Animals bred at this time are more likely to get pregnant and have multiple kids.…”
Section: Reproduction In Goatsmentioning
confidence: 99%